1900 Md. Laws 287-88 - (:unkn) unknown (My University, 1900)
General Powers, § 181: To regulate or prevent the storage of gunpowder, tar, pitch, resin, coal oil, benzene, turpentine, hemp, cotton, nitro-glycerine, dynamite, giant powder, petroleum, gasoline or gas, or any product thereof, or any other explosive or combustible material or any material which may seem to be dangerous.
Keywords: GUNPOWDER - STORAGE